INFORMATION TECHNOLOGY SERVICE MANAGEMENT PLANNING USING THE ITIL VERSION 3 FRAMEWORK IN PRABUMULIH CITY WORK TRAINING CENTER - Yulia Permata Sari; Tata Sutabri (Sean Institute, 2022)
The development of information technology has provided convenience for service users. One of the education or educational institutions is a means for the development and growth of students who direct and encourage in terms of achieving educational goals. Based on the explanation of RI Law number 20 of 2003 concerning National Education Standards article 35 (Paragraph 1). This service has not been integrated with one another. In this study using ITIL Version 3 as a framework with three stages, namely the first stage, the second stage and the third stage. The initial stage of the research consisted of literature studies, interviews and observations, the second stage was designing, and the third stage was preparing Service Level Management documents. The results of this study are information technology service management planning using ITIL Version 3 at the Prabumulih Vocational Training Center.